InSAR coseismic deformation field and seismogenic structure of the 2020 Mw6.0 Jiashi earthquake and the implication for the moderate-magnitude seismicity in the southwestern Tian Shan, western China - Wu, Danruo; Chen, Zhidan; Zimin, Mikhail (Frontiers in Earth Science, 2024)
The Kepingtage fold-and-thrust belt in the southwestern Tian Shan in western China hosted the 2020 Mw 6.0 Jiashi earthquake with no apparent surface ruptures. The thrust nappe structure in this region is characterized by moderate-magnitude (Mw5.5-6.5) seismicity, but the seismogenic mechanisms and controlling factors remain under investigation. In this study, we utilized Sentinel-1A synthetic aperture radar satellite data to reconstruct the InSAR coseismic deformation field of the 2020 Jiashi earthquake. To address the limitation imposed by residual orbital phases during the interferometric measurement, we proposed a novel automatic method that combines ascending and descending track data with terrain features for orbit refinement. Eight comparative tests were conducted to prove the effectiveness of the proposed method. Subsequently, we inverted the jointly constrained deformation field after orbit correction to obtain the fault geometric parameters and slip distribution. Our results show that the 2020 Jiashi earthquake is characterized by right-lateral transpressive motion. The smooth interference fringes demonstrate spatially continuous surface uplift and subsidence without detectable coseismic surface ruptures, with a maximum uplift of ∼0.08 m and a maximum subsidence of ∼0.03 m, caused by the subsurface folding due to deep seismic rupture. This event is best fitted by a north-dipping fault plane with a depth of 4.2 km, a dip angle of 11.6°, and a strike of 276° beneath the Keping thrust fault. In terms of various geometric parameters of the fault, the inversion results of this study are generally similar to the focal mechanism solution provided by USGS (MWb), but are different from the focal mechanism solutions of other institutions and previous research results. Combined with the published geological investigations and seismic reflection surveys, we suggest that the seismogenic structure of the 2020 Jiashi earthquake is the lower ramp of the Keping thrust fault and the abrupt fault bend between the lower and upper ramp may limit the propagation of the coseismic rupture to the surface. The limited rupture of this event is dominated by the irregularities in fault geometry along strike and dip, as well as the lower rock strength of the cover above the detachment, which contribute to a deeper understanding of the seismic behavior in fold-and-thrust belts and the moderate-magnitude seismicity in the southwestern Tian Shan region.